Liberalisation of network industries: Is the electricity sector an exception to the rule? - François Coppens; David Vivet (National Bank of Belgium, 2004)
For quite a long time, network industries used to be regarded as (natural) monopolies. This was due to these industries having some special characteristics. Network externalities and economies of scale in particular justified the (natural) monopoly thesis. Recently, however, a trend towards deregulation of such industries has been observed. This trend started with the successful introduction of competition in the telecommunications sector. The main reason behind this success is that the economies of scale have disappeared as a result of emerging new technologies. The successful deregulation in telecommunications is in line with micro-economic theory, which predicts an increase in efficiency and lower prices when markets are opened up to competition. The success in the telecommunications sector is often used as an argument for opening up other network industries to competition as well. In this paper we analyse whether this reasoning can be transposed to the electricity sector. It is argued that the two sectors, electricity and telecommunications, are similar in that they are both network industries which used to be characterised by economies of scale, and that technological progress might have put an end to this scale effect. There are however certain differences. Firstly, technological progress on the supply side was accompanied by a strong growth in demand in the telecommunications sector. This demand side effect is absent in electricity. Moreover, due to physical characteristics, the electricity sector seems to be more complicated: in order to introduce competition in the sector, it has to be split up into subsectors (production, transmission, distribution and supply). Competition is introduced in production and supply, transmission and distribution remain monopolies. This splitting up creates a new kind of costs, the so-called transaction costs. The paper is centered around two issues: (a) are the basic assumptions behind the theoretical model of the perfectly free market met in the deregulated subsectors? and (b) do the transaction costs (partly) offset possible price decreases in competitive segments ? There is no hard evidence that the hypotheses behind the theoretical model are met in the electricity sector, and there are strong indications that these transaction costs might be substantial. Moreover, in addition to the deregulation process, the electricity sector is also subject to other changes such as the internalisation of externalities (see the Kyoto protocol) and the debate on nuclear energy. These elements could exert an upward pressure on prices. Since electricity is ubiquitous, the deregulation process should be closely monitored.
Keywords: D23; D41; D42; D43; D62; L12; L13; L94; L96; 330; Welfare economics; market structure and pricing; organizational behaviour; transaction costs; property rights; Electric Utilities; Telecommunications.; Elektrizitätswirtschaft; Telekommunikation; Netzregulierung; Deregulierung; Transaktionskosten; Sachenrecht; Wohlfahrtsökonomik; Theorie